The Relationship Between Family Self Efficacy and the Success of Home Care - Gian Fitroh Hidayah; Hendri Hadiyanto; Asep Suryadin; Hadi Abdillah (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Family self-efficacy plays an essential role in determining the quality of home care provided to postoperative patients. Low self-efficacy may lead to inadequate care performance and hinder optimal recovery. Purpose: To determine the relationship between family self-efficacy and the success of home care among postoperative patients at RSUD Sekarwangi. Method: This study used a quantitative approach with a cross-sectional design. A total of 30 family members who provided home care for postoperative patients were included as respondents. The General Self Efficacy Scale (GSES) was used to measure self-efficacy, while the Resident Assessment Instrument Home Care (RAI-HC) assessed home care success. Analysis technique: Data were analyzed using the Chi-Square test to examine the relationship between variables. Results: Most respondents demonstrated good self-efficacy (73.3%) and good home care success (73.3%). The Chi Square test showed a significant relationship between family self-efficacy and home care success (p = 0.000; p < 0.05). Conclusion: There is a significant relationship between family self-efficacy and the success of home care among postoperative patients at RSUD Sekarwangi. Enhancing family education and strengthening confidence are recommended to improve home care quality and support optimal patient recovery.